Sosialisasi Pembuatan Pupuk Organik Cair (POC) dan Penyemaian Tanaman Obat Keluarga (TOGA) - Putri Astiti; Sunandie Eko Ginanjar; Gina Sofia Rahman; Suci Larassati Anjani (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Waste is remainder from people's daily activities. Waste that is not properly managed, will gradually become a serious problem for the environment. The aim of this community service is to give knowledge to the people of Loa Village on how to manage waste properly, by utilizing organic waste into Liquid Organic Fertilizer or Pupuk Organik Cair (POC) and understand the importance of Family Medicinal Herbs or Tanaman Obat Keluarga (TOGA) for the family use. The method used in this service is delivering material on how to make POC and planting TOGA. The results of this activity can be concluded that the people/residents of Loa Village who took part in the activity were able to understand well about how to make POC and the benefits obtained from POC and TOGA.